Early Season NFL Over/Under Bias. (April 2014) - DiFilippo, Michael; Krieger, Kevin; Davis, Justin; Fodor, Andy
Popular wisdom regarding athletics is that offenses are at a relative disadvantage in the early portion of seasons. The authors present evidence that this anecdotal belief holds true over the 2000-2010 National Football League (NFL) seasons. This is reflected in lower offensive yardage, fewer first downs, and fewer points scored. While total points scored are significantly lower in Week 1 of NFL seasons, bookmakers fail to reduce the total lines posted on these games. The authors find a strategy betting under total lines of all Week 1 games over the 2000-2010 NFL seasons yields a statistically significant return of 13.6% per game.